Preeclampsia, Hypoxia, Thrombosis, and Inflammation - Amir A. Shamshirsaz; Michael Paidas; Graciela Krikun (Journal of Pregnancy)
Reductions in uteroplacental flow initiate a cascade of molecular effects leading to hypoxia, thrombosis, inflammation, and endothelial cell dysfunction resulting in untoward pregnancy outcomes. In this review, we detail these effects and their relationship to preeclampsia (PE) and intrauterine growth restriction (IUGR).